Arteriovenous Cerebral High Flow Shunts in Children: From Genotype to Phenotype - Tas, Berivan; Starnoni, Daniele; Smajda, Stanislas; Vivanti, Alexandre J.; Adamsbaum, Catherine; Eyries, Mélanie; Melki, Judith; Tawk, Marcel; Ozanne, Augustin; Revencu, Nicole; Soubrier, Florent; Siala, Selima; et al. (Frontiers in Pediatrics, 2022)
Objective To study the genotypes and phenotypes of cerebral arteriovenous fistulas that drain or do not drain through the vein of Galen, and true vein of Galen aneurysmal malformations, in order to determine whether genotyping could help improve classification of these malformations and their management. Methods We carried out a retrospective review of genetic and phenotypic data in databases of four centers. All children with cerebral arteriovenous fistula or vein of Galen aneurysmal malformations aged below 18 years at onset were included. We recorded the nature of the genetic variant or absence of variant, age at onset, type of malformation, symptoms at onset (hemorrhage, neurological deficit, hydrocephalus, incidental, and heart failure), type of venous drainage and the long-term outcome. Results One hundred and fifteen children were included. Autosomal dominant variants were identified in 39% of patients. The most frequent variant affected was the RASA1 gene (25%) followed by EPHB4 (8%) and the HHT-associated genes (5%). HHT gene variants were only observed in pial arteriovenous fistula not draining into the vein of Galen; on the contrary, EPHB4 variants were only seen in genuine vein of Galen aneurysmal malformation. RASA1 variants were identified in all types of shunts. Conclusions EPHB4 variants seem specific to the vein of Galen aneurysmal malformation, RASA1 variants are associated with either pial arteriovenous fistulas or with genuine VGAM and HHT gene variants seem specific to pial arteriovenous fistulas. The genetic data helps to classify these malformations and to guide treatment toward lowest risk of post-operative cerebral ischemic-hemorrhagic complications.